Oxide growth and dissolution on 316L stainless steel during irradiation in high temperature water. (15th August 2019) - Hanbury, Rigel D.; Was, Gary S.
Highlights: Helium bubble marker layer yields accurate measurement of metal dissolution. 316 L corrosion decreases under proton irradiation. Dissolution is the dominant mode of corrosion under proton irradiation. Abstract: Helium was implanted in 316L stainless steel to produce a marker layer of bubbles to provide a reference for the assessment of oxidation and dissolution during proton irradiation in 320 °C hydrogenated water for 24 h and 72 h. Inner oxide thickness characterized by TEM dropped by a factor of 4.5 with irradiation. Marker layer measurements reveal a factor of 3 lower metal loss with irradiation. Metal loss increased without inner oxide growth between 24 h and 72 h of irradiation. Greater enrichment of chromium in the oxide under irradiation yields a more protective oxide film despite evidence of oxide dissolution.